Linkaging the indirect effects of exchange rate to economic growth and poverty through economic performance in developing countries - Lubis, Muhammad Riyadh Ghozali (Tanjong Malim, 2020)
Linkaging the indirect effects of exchange rate to economic growth and poverty through economic performance in developing countries by Lubis, Muhammad Riyadh Ghozali